Universal basic income on blockchain: the case of circles UBI - Papadimitropoulos, Vangelis; Perperidis, Giannis (Frontiers in Blockchain, 2024)
The paper reviews Circles UBI as an illustrative case study of implementing the idea of universal basic income (UBI) on Blockchain. Circles was born out of the Gnosis Chain as a more democratic alternative to Bitcoin, coupled with the ambitious political project of algorithmically distributing UBI. Backed by Gnosis Chain, Circles Coop was founded in 2020 to implement this idea in Berlin. Examining the failure of the Berlin pilot helps us draw substantial conclusions with regards to the implementation of UBI on Blockchain. UBI alone, on Blockchain or not, is not enough to solve the problems its proponents argue for. UBI would be helpful as a tool if plugged into a model of production embedded into a political strategy aiming to fix key problems of current societies such as gaping inequalities and climate change. We give a snapshot here of the model of open cooperativism as a counter-hegemonic political project vis-à-vis neoliberalism. Circles UBI could plug into the model of open cooperativism as a distribution and liquidity injection mechanism to foster the transition towards a commons-based ethical and sustainable post-capitalist economy.https://www.ubi.org/